The organization factors as barrier for sustainable Health Information Systems(HIS): a review - Mohamadali, Noor Azizah; Zahari, Nurul Aqilah (Elsevier, 2017)
Health Information Systems (HIS) helps in coordinating various activities within hospital through effective and efficient services. Malaysian Government began to introduce HIS in 1999 to cover both clinical and non-clinical information systems. Since then hospitals have been facing challenges to achieve the objectives of its introduction. Thus, it is important to understand determinants for successful implementation in order to ensure sustainable HIS. Various determinants render successful implementation, such as human factors, technology factors as well as organizational factors. However, understanding organizational factors become important, since the systems run within the organization itself. The other two factors; human and technology factors have been discussed elsewhere by the authors. Any issues pertaining to the organization if identified earlier will prevent implementation failure. Hence, this paper aims to provide a review of barriers associated with organization factors hindering the sustainability of HIS, and propose strategies required to minimize the issues discussed. Based on our review, this paper highlighted four main challenges from an organization perspective; high adoption cost, top management support, adequate infrastructure and security and privacy issues.